Analisis spasial terhadap kejadian demam berdarah dengue (DBD) di Indonesia: A systematic review - Ho, Veronika Angellina Hiberto; Wijayanti, Siwi Pramatama Mars; Rejeki, Dwi Sarwani Sri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a major public health problem in Indonesia, with significant regional variations in incidence. Despite the government's implementation of various control programs, DHF cases continue to exhibit specific spatial clustering patterns influenced by environmental and demographic factors. Purpose: To analyze the spatial distribution of dengue fever cases in Indonesia and identify environmental and climatic factors associated with dengue fever incidence through a spatial analysis approach. Method: This study followed the PRISMA guidelines and included articles published between January 2020 and December 2024. A literature search was conducted through the PubMed and SINTA databases using the keywords